Why They Choose Teaching: a Factor Analysis of Motives of Malaysian Teacher Trainees - Yaakub, Noran Fauziah (1990)
A study was carried out on 210 fourth semester teacher trainees specializing in primary school teaching from a teachers' college in Kuala Lumpur for the 1986/87 academic year to seek out their motives for taking up teaching. Results off actor analysis produced six factors, five of which were interpreted. Factor 1 touches on personal considerations for teaching; Factor 2 on the values of teaching; Factor 3 is altruistic in nature; Factor 4 refers to agreeable working conditions and Factor 5, influence 'received from key persons. Results are discussed in relation to Goldberg's theory of occupational choice and other 'related literature. The findings of the study have several implications on the selection of teacher trainees.